175 Patient Safety Indicator 04 Does not Consistently Identify Failure to Rescue in the Neurosurgical Population. (April 2023) - Azad, Tej D.; Rodriguez, Emily; Raj, Divyaansh; Xia, Yuanxuan; Materi, Joshua; Rincon Torroella, Jordina N.; Gonzalez, L. Fernando; Suarez, Jose; Tamargo, Rafael Jesus; Brem, Henry; Haut, Elliot; Bettegowda, Chetan
Abstract : INTRODUCTION: Patient safety indicator (PSI) 04 is a quality index designed by the Agency for Health Research and Quality to measure Failure to Rescue (FTR). PSI 04 has been scrutinized for inaccurately measuring FTR, a framework developed to capture a hospital's ability to identify and manage preventable complications and post-operative mortality. METHODS: We conducted a single-center retrospective cohort study. We identified patients from 1/12/2017-6/1/2021 who sustained a PSI 04-attributed complication (pneumonia, deep venous thrombosis/pulmonary embolism (DVT/PE), sepsis, shock/cardiac arrest, or gastrointestinal (GI) hemorrhage/acute ulcer), underwent a neurosurgical procedure, and had inpatient mortality. The primary outcome was whether the attributed PSI 04 designation was the primary driver of mortality. RESULTS: We identified 67 patients who met PSI 04 criteria (median age, 61; female sex, 43.4%). Nearly 20% of patients met the PSI complication criteria prior to admission. Patients who underwent emergent bedside procedures were more likely to present with poor GCS (P = 0.016), more likely to be intubated prior to admission (P = 0.016), and less likely to have mortality due to a PSI 04-related complication (P = 0.002). PSI 04-related complications were identified as the cause of death in only 43.2% of cases. Procedures occurring in the interventional radiology suite (OR, 23.2; 95% CI, 3.5-229.3; P = 0.003) or the operating room (OR, 6.2; 95% CI, 1.25-39.5; P = 0.03) were more likely to have mortality due to a PSI 04-related complication compared to bedside procedures. CONCLUSIONS: Most neurosurgical procedures meeting PSI 04 criteria took place outside of a traditional operating room and may capture a fundamentally different patient population. 65.7% of patients were inappropriately flagged as meeting PSI 04 criteria. PSI 04 currently identifies patients with complications unrelated to operating room procedures. Improvement in patient safety within neurosurgery necessitates the development of a subspecialty specific measure to capture FTR.